Eldelumab [anti-interferon-γ-inducible protein-10 antibody] Induction Therapy for Active Crohn's Disease: a Randomised, Double-blind, Placebo-controlled Phase IIa Study. (22nd February 2017) - Sandborn, William J.; Rutgeerts, Paul; Colombel, Jean-Frédéric; Ghosh, Subrata; Petryka, Robert; Sands, Bruce E.; Mitra, Pranab; Luo, Allison
Abstract: Background and Aims: This 11-week Phase IIa induction study evaluated the efficacy and safety of eldelumab in patients with active Crohn's disease. Methods: Adults with Crohn's Disease Activity Index 220–450 were randomised 1:1:1 to placebo or eldelumab 10 or 20 mg/kg intravenously on Days 1 and 8, and alternate weeks thereafter. All patients underwent ileocolonoscopy at baseline. Patients with active inflammation according to the Simplified Endoscopic Score for Crohn's Disease criteria [the originally planned endoscopy cohort] underwent another ileocolonoscopy at Week 11 at the investigator's discretion. All ileocolonoscopies were centrally read. The primary objective was identification of the eldelumab target exposure for induction of remission [absolute Crohn's Disease Activity Index score < 150]. Rates of clinical response [reduction of ≥ 100 from baseline or absolute score < 150 Crohn's Disease Activity Index], remission, and endoscopic improvements were also assessed. Results: A total of 121 patients were randomised. The eldelumab exposure–remission relationship was not significant at Week 11. Numerically higher remission and response rates were reported with eldelumab 20 mg/kg [29.3% and 41.5%, respectively] and 10 mg/kg [22.5% and 47.5%] versus placebo [20.0% and 35.0%]. A higher proportion of patients with a baseline Simplified Endoscopic Score for Crohn's Disease > 2 who received eldelumab achieved a 50% improvement in score and greater reductions from baseline endoscopy scores overall versus placebo. Adverse events were comparable across treatment groups. Conclusions: No exposure–remission relationship was seen with eldelumab. Eldelumab induction treatment demonstrated trends towards clinical and endoscopic efficacy. Safety was consistent with that reported previously. ClinicalTrials.gov identifier: NCT01466374.